Criminal Liability in the Crime of Corruption in Land Acquisition for Campus Development of Imam Bonjol Padang State Islamic University - Sarah Qurrata A’yun; Elwi Danil; Hengki Andora (Dinasti Research, 2025)
Land acquisition plays an important role in development and requires the involvement of a notary to ensure the legality of the transaction. However, in practice, notaries can be involved in corruption crimes, such as falsifying documents and inflating prices. This study analyzes the criminal liability of notaries in the case of corruption in land acquisition of UIN Imam Bonjol Padang Campus with a normative juridical approach and case studies. The results of the study show that notaries who abuse their authority can be subject to criminal sanctions. Therefore, strict supervision and stricter regulations are needed to prevent corruption in land procurement and maintain the integrity of the notary profession